Pendidikan Karakter Akhlakul Karimah di Pesantren At-Taubah Dr KH Ishak Muzawwir Karawang Indonesia - Cucu Komariah (Departement of Mathematics Education, 2024)
Character education of akhlakul karimah at Pesantren At-Taubah Dr KH Ishak Muzawwir Karawang Indonesia is carried out through habituation such as reading the Qur'an, memorizing verses of the Qur'an, behaving politely and having manners according to Islamic teachings. The purpose of this study was to analyze the implementation of akhlakul karimah character education at At-Taubah Islamic Boarding School. The research method used is a qualitative approach, types and sources of data using primary data and secondary data, data collection techniques using observation, interviews and documentation studies. Data analysis techniques use data triangulation where data is selected that is important and appropriate and then processed to draw conclusions. The result of the research is that students at the At-Taubah DR KH Ishak Muzawwir pesantren have implemented akhlakul karimah character education through habituation and role models from teachers. There are three education programs, the first is daily, monthly and annual programs. The inhibiting factor is that not all students come from the pesantren. Supporting factors are pesantren leaders and teachers who give examples of akhlakul karimah, extensive infrastructure facilities around 3 hectares. A beautiful conducive place away from the hustle and bustle of the crowd. Gentle pesantren leaders and teachers, habituation of akhlakul karimah through habituation.